Evolution of Aluminium-Tin Multi Material Drilling Process on Bench Press Drill Machine - Naveen Kumar; Lokesh Singh (International Journal of Scientific Research in Mechanical and Materials Engineering, 2024)
The evolution of the aluminium-tin multi-material drilling process on a bench press drill machine has been a crucial area of research aimed at enhancing drilling efficiency and quality in heterogeneous material stacks. This study investigates the optimization of drilling parameters such as cutting speed, feed rate, and drill bit geometry to achieve improved tool life and hole quality while drilling aluminium-tin composites. Experimental methodologies involving various combinations of these parameters have been employed to analyze their effects on drilling forces, surface roughness, and burr formation. The findings contribute to a deeper understanding of the drilling behavior of aluminium-tin multi-materials and provide insights into the development of strategies for optimizing drilling processes on bench press drill machines, thereby advancing manufacturing capabilities in industries requiring precision drilling of composite material give a comprehensive understanding of the art in multi-material drilling of aluminum-tin plates, offering insights into future research directions and industrial applications in aerospace, automotive, and other high-performance sectors.